Death rides a pony - Miller, Carol, 1972- (Miller, Carol, 1972- Fortune telling mysteries, 2022)
"Sisters Hope and Summer Bailey run Bailey's Boutique, a mystic shop in Asheville, North Carolina. The annual charity festival is approaching, and the sisters are roped in to offering fortune telling to raise money. Before proceedings can begin, Summer receives a bad Tarot card reading. She fears she'll be left destitute from her upcoming divorce battle as the realtor charged with selling her and her soon-to-be ex-husband's home, Davis Scott, keeps making unwelcome appearances. Davis's most troublesome appearance comes when he's found dead at the festival. Davis had a bad reputation amongst the Ashville community, but who would go to the lengths of killing him . . . and during a charity event, no less! The Tarot cards predicted a death, but do they hold clues to who the murder is?"--